2019
DOI: 10.1051/metal/2018082
|View full text |Cite
|
Sign up to set email alerts
|

In situ observation on microstructure evolution of 22MnB5 in hot stamping process

Abstract: High temperature confocal laser scanning microscopy (CLSM) was used to investigate the microstructure evolution of high-strength boron steel 22MnB5 during hot stamping. The experimental results show that it is complete austenitized at temperatures about 810 °C during the heating process. Most of the initial austenite grain size is small and locally coarse. At 920 °C to 1000 °C, the phenomenon of B remelted and solidified was observed which played a very good pinning role at the austenite grain boundary, preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The blank temperature, by starting too close to both electrically powered mold halves was considered with T Close , in order to ensure uniform test conditions and the comparability of all measured temperatures profiles. In addition, the start temperature for the formation of martensite (~400 • C) [27] was indicated as T Ms . The recorded time interval between both temperatures values was taken into account by ∆t.…”
Section: Analysis On the Thermo-mechanical Performancementioning
confidence: 99%
“…The blank temperature, by starting too close to both electrically powered mold halves was considered with T Close , in order to ensure uniform test conditions and the comparability of all measured temperatures profiles. In addition, the start temperature for the formation of martensite (~400 • C) [27] was indicated as T Ms . The recorded time interval between both temperatures values was taken into account by ∆t.…”
Section: Analysis On the Thermo-mechanical Performancementioning
confidence: 99%
“…[ 12,13 ] During this last quenching phase, the material undergoes a martensitic transformation, giving the component high mechanical strength. [ 13–15 ] This allows to adopt thinner blanks to reduce the overall weight of the vehicle.…”
Section: Introductionmentioning
confidence: 99%
“…Mu et al [16] compared and analyzed the mechanical properties of 30MnB5 and 22MnB5, and the mechanical properties of the hot-formed steel after quenching were the best when the austenitizing temperature was kept at 900 • C and the holding time was 3-5 min. Kong et al [17] pointed out that the cooling rate has a significant effect on the hardness of 22MnB5 steel after quenching. Zhou et al [18] concluded that the cooling rate during quenching should exceed 40 • C/s in order to obtain higher strength 22MnB5 hot forming steel.…”
Section: Introductionmentioning
confidence: 99%